Experimental evaluation of the lateral load distribution in the elastic-plastic phase of timber-steel hybrid structures with a novel light timber-steel diaphragm. Issue 8 (June 2019) - Ma, Zhong; He, Minjuan; Ma, Renle; Li, Zheng; Zhang, Linlin
A cyclic loading experiment involving a timber-steel hybrid structure consisting of a steel frame and a novel light timber-steel diaphragm is presented to quantify the flexibility of the diaphragm and its ability to distribute lateral loads in the elastic-plastic phase of the structure. A lateral load-distribution factor was proposed, and its relationship to the ratio of the stiffness of the diaphragm to that of the lateral load-resisting elements was investigated. The diaphragm was classified based on these variables. The results indicated that the failure modes of the structure were associated with the forms of damage experienced by the lateral load-resisting elements, whereas little damage was observed for the diaphragm. The diaphragm exhibited the ability to continuously adjust the distribution of lateral loads to each lateral load-resisting element; accordingly, each lateral load-resisting element had approximately the same shear force, the same lateral stiffness, and the same lateral displacement during the loading process. As the lateral displacement increased, the stiffness ratio and load-distribution factor both gradually increased, and the diaphragm correspondingly changed from semi-rigid to rigid. At times, as the lateral displacement increased, the diaphragm rapidly became rigid, and it was unnecessarily rigid during the initial loading phase when the in-plane stiffness reached a certain threshold.